School health approach to teaching and learning of students - Yu.S. Lukianova (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2015)
Purpose: disclosure of health-ways for teaching and learning of students. Material: analysis of the publications of domestic and foreign authors. Results: The article is devoted to the implementation of healthy way approach to the educational process, namely, the rational organization of training aimed at keeping the dynamics of human health, the prevention of mental fatigue and overload, increase adaptive reserves of the body of the person; intensification of teaching and learning of students (application-is controversial dialogue, training, game forms and methods of training, participation in project activities, the work of pedagogical workshops) that stimulates emotional accommodation and understanding of knowledge, helps students acquire personal-relevant knowledge and experience; use of health effect of artistic and practical (music, painting) activities of students. Conclusions: highlights the key towards the implementation of health-promoting approach to the educational process.